Modernism – Postmodernism – Neo-Modernism (Narrative Strategies in the German-Language Novel of the 21st Century) - G.A. Frolov; E.M. Shastina (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with specific features of the narrative strategies in the German-language novel of the 21st century which is regarded as a phenomenon of the whole contemporary literary process. The poetics of novels written by contemporary Austrian writers (Daniel Kehlmann’s Measuring the World (Die Vermessung der Welt) and Christoph Ransmayr’s The Flying Mountain (Der fliegende Berg)) is presented as a dynamic force with the narrative principles and elements of different types of paradigms, including modernism (subjective perspective and narration), realistic writing in its traditional form, and postmodernism (synthesis of the fictional and non-fictional, intertextual irony, and metaplay with the text). The novels under discussion are defined as neo-modernist metanarratives, where the authors of the paper disclose both radical literature experiments and, at the same time, repetition in the forms and tendencies already familiar and well-studied in modernism and postmodernism. The study of Daniel Kehlmann’s and Christoph Ransmayr’s novels is significant and important, because it helps to identify the typical narrative strategies of the Austrian novel in the 21st century, as well as to understand the objective laws of the development of German-language fiction and Western literature in general.